2016
DOI: 10.2204/iodp.proc.340.204.2016
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis: stratigraphy and age control for IODP Sites U1394, U1395, and U1396 offshore Montserrat in the Lesser Antilles

Abstract: This data report focuses on Holes U1394B, U1395B, and U1396C located offshore Montserrat. These holes were drilled during Integrated Ocean Drilling Program Expedition 340 and contain deposits associated with the growth and decay of the volcanic island of Montserrat. Hole U1394B dates to ~353 ka and is composed of 17 bioclastic turbidites, 24 mixed turbidites, 55 volcaniclastic turbidites, and 32 tephra fall layers within a background stratigraphy of hemipelagic marine mud. Hole U1395B dates to older than 1 Ma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 48 publications
7
21
0
Order By: Relevance
“…40 Ar/ 39 Ar dating (Harford et al, 2002;Brown and Davidson 2008) and stratigraphic studies (Rea et al, 1975;Baker et al, 1985;Wadge and Isaacs 1988;Roobol and Smith 1998;Smith 2007) indicate andesitic subaerial activity at Soufrière Hills since ~290 ka, is dominated by effusive eruptions, and interrupted by a brief interlude of basaltic volcanism at the South Soufriere Hills at ~130 ka (Harford et al, 2002;Cassidy et al, 2015). Offshore studies may suggest volcanism occurred earlier at Soufrière Hills (Coussens et al, 2016a(Coussens et al, , 2016bJutzeler et al, 2016). Prior to this, current dates for subaerial activity at Centre Hills span the interval 0.95-0.55 Ma, and 2.6-1.2 Ma for Silver Hills, the oldest volcanic centre on Montserrat (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 Ar/ 39 Ar dating (Harford et al, 2002;Brown and Davidson 2008) and stratigraphic studies (Rea et al, 1975;Baker et al, 1985;Wadge and Isaacs 1988;Roobol and Smith 1998;Smith 2007) indicate andesitic subaerial activity at Soufrière Hills since ~290 ka, is dominated by effusive eruptions, and interrupted by a brief interlude of basaltic volcanism at the South Soufriere Hills at ~130 ka (Harford et al, 2002;Cassidy et al, 2015). Offshore studies may suggest volcanism occurred earlier at Soufrière Hills (Coussens et al, 2016a(Coussens et al, , 2016bJutzeler et al, 2016). Prior to this, current dates for subaerial activity at Centre Hills span the interval 0.95-0.55 Ma, and 2.6-1.2 Ma for Silver Hills, the oldest volcanic centre on Montserrat (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Prior to this, current dates for subaerial activity at Centre Hills span the interval 0.95-0.55 Ma, and 2.6-1.2 Ma for Silver Hills, the oldest volcanic centre on Montserrat (Figure 1). Volcaniclastic deposits within the offshore sedimentary stratigraphy (e.g., Watt et al, 2012;Trofimovs et al, 2013) provide a more complete record of volcanic activity at Montserrat (Coussens et al, 2016a(Coussens et al, , 2016b, and suggest a more continuous level of volcanism than indicated by dated subaerial units (which imply gaps on 10 4 -year timescales between activity at the individual volcanic centres). However, many of these offshore deposits are mixed volcaniclastic turbidites, potentially derived from a range of primary and secondary volcanic processes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Eruptive products from Guadeloupe can be distinguished using lead isotopes because Guadeloupe has a higher radiogenic lead component [ Cassidy et al ., ; Palmer et al ., ], and Coussens et al . [] use Pb isotopes to show that most tephra layers recorded within Hole U1395 B are likely to be from Montserrat. Over the past 1 Ma [ Samper et al ., ], volcanic activity occurred in the southeast of Guadeloupe at Grande Découverte Soufrière, producing landslides that have mostly traveled westward into a canyon system [ Samper et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…the graben, volcanism extends back to the late Pliocene at~2.8 Ma (Samper et al, 2007). Submarine pyroclastic deposits SE of Montserrat extend to at least 4 Ma (Coussens et al, 2016) in IODP core U1396, but the volcanic center for this early volcanism has not been identified.…”
Section: Evolution and Subsidence Of The Kahouanne Seamountsmentioning
confidence: 99%
“…Regardless of their origin, intra-arc basin formation in subduction zones leads to important sedimentary depocenters where thick accumulations of volcaniclastic and biogenic sediments build up rapidly owing to the proximity of volcanic and associated carbonate platform sources (Clift and ODP Leg 135 Scientific Party, 1994;Carey and Schneider, 2011;Carey, 2000;Trofimovs et al, 2010). For example, IODP drilling and seismic surveys to the southeast of Montserrat have identified several hundred meters of interbedded volcaniclastic and hemipelagic deposits derived from a variety of masswasting and eruption-related processes that have shaped the Centre Hills and Soufrière Hills volcanoes on Montserrat (Lebas et al, 2011;Watt et al, 2012;Le Friant et al, 2015;Coussens et al, 2016) (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%